Evangélicos e voto legislativo: Diversidade confessional e voto em deputados da bancada evangélica no Brasil - Rodrigo Rodrigues-Silveira; Emerson Urizzi Cervi (Latin American Research Review, 2019)
This article analyzes the impact of the diversity of evangelical denominations at the municipal level on the proportion of votes obtained by those members of Congress belonging to this demographic group. To reach this goal, we employ demographic and electoral data, as well as the composition of the evangelical caucus in the 2014 elections to Congress. We compare the effect of confessional diversity in the municipalities between two groups of elected representatives: evangelicals and nonevangelicals. We found that the higher the number of evangelical churches in the municipality, the more significant the proportion of votes obtained by the evangelical deputies. Controlling the effect of confessional diversity on electoral performance by other members of Congress also enabled us to confirm that the observed effect was exclusive to evangelical deputies and not replicated in other representatives. The results provide consistent empirical evidence in favor of the hypothesis that there is complementarity between religious denominations about voting.   Resumo Este artigo investiga o impacto da diversidade de denominações religiosas de cunho evangélico no nível municipal sobre a proporção de votos obtidos pelos deputados eleitos que representam esse grupo demográfico. Para alcançar tais propósitos, utilizamos dados demográficos e eleitorais, assim como relativos à composição da bancada evangélica no congresso para as eleições de 2014. Comparamos o efeito da diversidade confessional nos municípios entre dois grupos de deputados eleitos: evangélicos e não-evangélicos. Verificamos que quanto o maior número de igrejas evangélicas com representação no município, maior a proporção de votos obtida pelos deputados evangélicos. O controle do efeito da diversidade confessional no desempenho eleitoral pelos outros parlamentares também nos permitiu confirmar que o efeito observado era exclusivo de deputados evangélicos, não sendo reproduzido em outros representantes. Os resultados aportam evidências empíricas consistentes a favor da hipótese de que existe complementaridade entre denominações religiosas no que se refere ao voto.